Taxonomic revision of the genus Hemigyrus Brunner von Wattenwyl, 1893 (Orthoptera: Tettigoniidae: Pseudophyllinae) - Xie, Hui-Cong; Wang, Han-Qiang; Zong, Jing-Song; Li, Kai; He, Zhu-Qing (Zootaxa, 2022)
Hemigyrus was established by Brunner von Wattenwyl in 1893. In this study, we collected samples from Chongqing, Guangxi, Hainan, Sichuan, Tibet and Yunnan of China, and reconstructed phylogenetic tree based on COI gene. The results supported the classification of dividing this genus into two subgenera: Tomomima and Hemigyrus. With larger size and evidently branched phylogenetic position, a new subspecies H. (T.) spinosus robustus subsp. nov. Xie, Wang & He is described here. H. (H.) acutifolius is firstly reported from China. Males of H. (H.) amplus and H. (H.) acutifolius, females of H. (H.) minor are described for the first time. All materials were deposited in Biological History Museum of East China Normal University (ECNU) and the Shanghai Entomological Museum, Chinese Academy of Sciences (SEM).